What are gender differences in lower limb muscle activity during jump-landing tasks? A systematic review and meta-analysis - Mohammad Seyedahmadi; Hooman Minoonejad; Mohammad Karimizadeh Ardakani; Zahra Heidari; Mohammad Bayattork; Hadi Akbari (BMC, 2022)
Abstract Background Gender differences in muscle activity during landing have been proposed as a possible contributing factor to the greater incidence of anterior cruciate ligament injuries in women. Conflicting results among a few studies in this regard makes it impossible to reach correct conclusions. Objectives The aim of this study was systematic review and the meta-analysis of previous studies which have compared the electromyographic activity of lower limb muscles in gluteus muscles (maximus and medius), quadriceps (rectus femoris, vastus medialis and lateralis), hamstrings (biceps femoris and semimembranosus), and gastrocnemius in men and women in jump-landing task. Methods A systematic search of the PubMed, SCOPUS, Science Direct databases was performed for eligible articles in October 2020. Cross-sectional studies that compared the muscle activity of male and female athletes without a history of previous injury in the jump-landing task were included. Unisex and non-athlete's studies were extracted from the included studies. The data were synthesized using a fixed and random effects model. Results Eight studies involving 145 participants were included. All participants were people who participated in regular exercises. The meta-analysis of timing and muscle activity was performed in the feedforward (pre contact) and feedback (post contact) stages. There were no significant differences in the muscle activity of biceps femoris (MD = −12.01; 95% CI − 51.49 to 27.47; p = 0.55; I2 = 87%), vastus medialis (MD = −53.46; 95% CI − 129.73 to 22.81; p = 0.17; I2 = 91%), semimembranosus (MD = 1.81; 95% CI − 6.44 to 10.07; p = 0.67; I2 = 0%), gluteus medius (MD = −3.14; 95% CI − 14.24 to 7.96; p = 0.58; I2 = 48%), and rectus femoris (MD = −5.83; 95% CI − 14.57 to 2.92; p = 0.19; I2 = 87%) in the pre contact phase between two sexes. There was a significant difference between men and women in the activity of vastus lateralis muscle in the post contact phase (MD = −34.90; 95% CI − 48.23 to − 21.57). No significant difference was observed between the men and women in the timing of semimembranosus (MD = 23.53; 95% CI − 14.49 to 61.54; p = 0.23; I2 = 56%) and biceps femoris muscle activity (MD = −46.84; 95% CI − 97.50 to 3.83; p = 0.07; I2 = 82%). Conclusion The results showed that in all lower limb muscles except vastus lateralis there were no significant differences between muscle activity and muscle contraction timing in both sexes before and after foot contact. Therefore, it can be concluded that the reason for the greater susceptibility of ACL injuries in women than men is maybe related to other factors such as biomechanical and hormonal. Additional good quality research in this regard is required to strengthen these conclusions.